Penambatan Molekul Senyawa Swietemacrophyllanin dari Kulit Batang Mahoni (Swietenia macrophylla King,) sebagai Inhibitor Enzim Alfa Glukosidase - Arini Khaerunnisa; Ratna Djamil; Lilik Sulastri; Tarso Rudiana; Partomuan Simanjuntak (UIN Syarif Hidayatullah Jakarta, 2023)
Mahogany (Swietenia macrophylla King.) is one of the plants used as an antidiabetic agent. 96% ethanol extract of S. macrophylla stem bark can inhibit the α-glucosidase enzyme. Methanol and aqueous extracts of S. macrophylla stem bark can reduce rat blood glucose levels induced by streptozotocin. Molecular docking is one of the most widely used structural-based drug design strategies due to its wide application in the analysis of binding energy and molecular interactions between drug compounds and receptors. This study aims to identify the compounds in the stem bark of S. macrophylla and analyze the molecular anchoring of the compounds produced by the aid. The research was carried out by means of the water fraction of the stem bark of S. macrophylla and was purified by column chromatography. Fraction 2 was identified by LCMS-MS. Molecular docking using AutoDock 4.2.6. The results of Fraction 2 showed the presence of catechins, evodionol, swietemacrophyllanin, swietenitin K and β-sitosterol. The results of an in-silico study showed that swietemacrophyllanin provided a better affinity than acarbose with a binding energy value of -8.57 kcal/mol and an inhibition constant of 0.52 µM. Forms hydrogen bonds with catalytic residues (Glu277 and Asp352) from the active site of the α-glucosidase enzyme. Swietemacrophyllanin has potential as an antidiabetic agent